The Physics of Quantum World of Particles - Kaur, Varinderjit (Journal of Advanced Research in Electronics Engineering and Technology; Vol 11 No 2 (2024): Journal of Advanced Research in Electronics Engineering and Technology, 2024)
The quantum world has always ignited human curiosity to unveil and speculate on the fascinati ng secrets of microscopic parti cles. This curiosity has opened a window to other branches of physics pushing the boundaries of classical understanding. After years of experimentati on and analysis, scienti sts revealed that at microscopic dimensions, Newtonian mechanics failed not only quantitatively but even qualitati vely and conceptually, clearing the way for new ideas. The nature of the diff erence between Newtonian mechanics and quantum mechanics is presented, with the core difference being the inherently probabilisti c nature of quantum mechanics. This probabilisti c foundati on has led to revolutionary concepts like wave-particle duality and entanglement, fundamentally challenging classical ideas of causality and locality. The present article provides a well-focused and comprehensive overview of foundation ideas, concepts, and applications of quantum mechanics that make it principally different from Newtonian mechanics.